1991
DOI: 10.1002/prot.340110206
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric inclusion by de novo designed proteins: Fluorescence probe studies on amphiphilic α‐helix bundles

Abstract: The inclusion feature and supersecondary structure of the de novo designed proteins which are constructed with several amphiphilic alpha-helices and flexible linkage parts were investigated with fluorescence probes. Five types of small proteins (or peptides) have been designed, which are composed of 2, 3, 4, 4, and 6 helices, respectively, and are linked with only linear junctions except for one of 4-helix proteins. All of these proteins have inclusion ability for hydrophobic fluorophores. Further, by the anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 23 publications
2
7
0
Order By: Relevance
“…Previously the authors reported that the size of the helix bundle protein including the fluorescence probe is 3.0-3.5 nm (axial) X 3.0-4.0 nm (equatorial) . 4 The experimental results for the size of the peptide-protein assemblies is almost similar or slightly larger than this. Considering that the assemblies are 1 : 1 complexes and both the peptides and P4W have an a-helical structure, it is reasonable to assume that the assemblies have complexed helix bundle structures.…”
Section: Resultssupporting
confidence: 51%
“…Previously the authors reported that the size of the helix bundle protein including the fluorescence probe is 3.0-3.5 nm (axial) X 3.0-4.0 nm (equatorial) . 4 The experimental results for the size of the peptide-protein assemblies is almost similar or slightly larger than this. Considering that the assemblies are 1 : 1 complexes and both the peptides and P4W have an a-helical structure, it is reasonable to assume that the assemblies have complexed helix bundle structures.…”
Section: Resultssupporting
confidence: 51%
“…When this probe combines with various molten globular protein forms, smaller intensity increases, typically 10-to 150-fold, and smaller blue-shifts, typically to the 460-490 nm range, are observed. The blue-shifts and intensity increases are evidently the result of ANS becoming associated with the nonpolar, nonrigidly packed regions of the molten globular forms (Semisotnov et al, 1991;Morii et al, 1991;Handel et al, 1993).…”
Section: Discussionmentioning
confidence: 97%
“…The fluorescent molecule 1 -anilinonaphthalene-8-sulfonate (ANS) has been used to probe the molten globule state (Semisotnov et al, 1991;Morii et al, 1991;Handel et al, 1993). Classical studies show that, as the ANS probe moves from water into the heme binding pocket in apomyoglobin, there is an increase in intensity of about 245-fold and a blueshift from 515 nm in water to 454 nm when in the binding pocket (Stryer, 1965).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the ®nding of this new a-helical motif should provide a new insight into the folding pathway of a-helical proteins. Moreover, a-helical motifs have been extensively studied as prime candidates for attempts at de novo design of proteins with novel properties (DeGrado et al, 1989;Cohen & Parry, 1990;Hecht et al, 1990;Morii et al, 1991;Kamtekar et al, 1993). To this aim, the a-antiparallel helix scaffold present in the 3D structure of p8 MTCP1 should constitute a very useful tool: when compared to classical a-helical bundles, the disul-®de bonds should provide most of the stabilization energy, leaving a larger part of the protein structure available for mutations.…”
Section: Discussionmentioning
confidence: 99%